Assessment of the Midwifery Students' Clinical Competency Before Internship Program in the Field Based on the Objective Structured Clinical Examination - Malakooti, Narges (Iran J Nurs Midwifery Res, 2018)
BACKGROUND: One of the important goals of clinical education is to promote the level of students' clinical skills. About 50% of the midwifery education is focused on clinical education, which has a great importance in shaping the professional skills of the students. The aim of this study was to determine the ability of students in some practical skills, before internship program in the field, using objective structured clinical examination (OSCE). MATERIALS AND METHODS: This research was a descriptive cross-sectional study with a single-stage, multivariate prospective design. Twenty-seven midwifery students from the Isfahan University of Medical Sciences who were in their sixth semester were selected by convenience sampling during the second semester of 2015–2016 educational year. OSCE was executed at skill laboratories in 8 stations during one day, and researcher-made checklists were used; their content and face validity were approved and their reliability was confirmed by a Cronbach's alpha coefficient of 0.97. Data analysis was performed by SPSS19. RESULTS: Results showed that the level of students' skills at pelvic exam station was 39.97%, at bladder catheterization was 66.92%, at Leopold was 42.7%, at fetal ECG interpretation was 50.49%, at physical examination was 21.30%, at fetal resuscitation was 48.81%, at breast examination was 56.32%, and at answering the questions was 23.49%. CONCLUSIONS: Results show that students gained a score of less than 50% in most skills. Therefore, they are not efficiently skilled for these essential clinical skills. Nonetheless, these procedures need the minimum skills that are required from students after graduation and before entering the working environment in hospitals and health centers. Therefore, more attention should be paid to these skills while planning internship programs before students enter the field. Also, more attention is required while teachers teach these skills and students are supposed to regard their weaknesses in these skills.